Streamlining of Processes and Its Impact on the Issuance Time of the Dean’s Resolution for Approval of Externally Financed Projects in a Public University - Cruz Chuquizuta, Consuelo (2023)
This paper addresses the question “How does the streamlining of processes based on the analysis of activities and staff awareness-raising impact the issuance times of the Dean’s Resolution of an agreement and/or contract in a public university?” A system was implemented to streamline processes in the issuance times of the Dean’s Resolution for approval of externally sponsored projects. Database review was used as the data collection technique. The data were processes by means of the RStudio interface. A significant reduction in the time required to issue the Dean’s Resolution for the approval of an agreement and/or contract was obtained as the final result.